If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5) + x = 4 Reorder the terms: (-5 + 2x) + x = 4 Remove parenthesis around (-5 + 2x) -5 + 2x + x = 4 Combine like terms: 2x + x = 3x -5 + 3x = 4 Solving -5 + 3x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 4 + 5 3x = 4 + 5 Combine like terms: 4 + 5 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 3Y^2-5=2Y | | 1+3x-x=-4+2x | | 6x^2+4x+10=54.16 | | 7x+12=3x-8 | | 5x=2x+3x | | 3-(2x-3)/3=(5-x)/2 | | 2x-5(2x+3)=2x+5 | | x^2-2xy+2y^2+2x-8y+10=0 | | 2x^2+5x-88=0 | | f(-x)=x^2-6x-4 | | 2x+3x=1235 | | x-3x-5x=-49 | | 8x-(3x-3)=18 | | f(x+8)=x^2-6x-4 | | 8a^4-4a^3+2a^2= | | 2y-5+7y=-32 | | -2n+18=5n-24 | | 2x+8=6x+24 | | 5w^2-14=3 | | 8m-5=25-2m | | -6X-4=12 | | 5x^2-18x+81=0 | | -100=12+-4 | | -(x+3)=2x-6 | | 5x^2-18x+81=90 | | 5t-16=48 | | b^2=144 | | -70=-5(6n-4) | | 10x^2=2x+3 | | 5x*3+(3*5)=3x-9*(6-9) | | 5x*3+(3*5)=3x-9 | | 7=9x-2(7x+9) |